2011
DOI: 10.1016/j.exer.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sphere formation from corneal keratocytes and phenotype specific markers

Abstract: The keratocytes are specialized mesenchymal cells that produce and maintain the extracellular matrix of the corneal stroma. With a typical dendritic and flattened appearance, these cells can morph into fibroblasts and myofibroblasts upon injury, and produce abnormal or fibrotic extracellular matrices detrimental to corneal transparency. Insights into mechanisms that regulate these phenotypic switches and optimal culture conditions that preserve the keratocyte phenotype are important for tissue engineering of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Similarly, we recently showed that primary cells extracted from donor human corneas could be plated overnight in growth factor and serum-free DMEM: F12 for attachment and subsequently grown in the presence of ITS and phosphoascorbic acid expressed keratocan [32]. However, when we used this approach on freshly isolated stromal cells from keratoconus corneas, cell death was unacceptably high at the early stages and ultimately led to poor total cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we recently showed that primary cells extracted from donor human corneas could be plated overnight in growth factor and serum-free DMEM: F12 for attachment and subsequently grown in the presence of ITS and phosphoascorbic acid expressed keratocan [32]. However, when we used this approach on freshly isolated stromal cells from keratoconus corneas, cell death was unacceptably high at the early stages and ultimately led to poor total cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…These cells did not express α-SMA (Figure 1B). CDH5 was selected as a specific keratocyte marker since Scott et al [13] showed CDH5 was expressed only by keratocytes not by fibroblasts. Human lung fibroblasts treated by transforming growth factor beta (TGF-β) were used as positive control for α-SMA.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, stromal cells were cultured in keratocyte growth medium (KGM) containing DMEM/F12 (Invitrogen-Gibco) with 10 ng/ml fibroblast growth factor 2(FGF2, Sigma-Aldrich), 1X insulin, transferrin, selenium (ITS, Invitrogen), 1 mM ascorbic acid-2-phosphate (Sigma-Aldrich), and 100 unit/ml penicillin (GIBCO), 100 μg/mL streptomycin (GIBCO). The cells were incubated at 37°C with 5% humidified CO 2 , and the medium was changed every 3~4 days [13]. When 80%–90% confluence achieved, they were trypsinized, subcultured and used for co-culture as described below.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with the plasticity observed in serum-free reversion of fibrotic corneal cells. 34 Thus, the addition of additional TGF-b would cause any cells that had begun to exhibit the native phenotype to once again revert. Cell reversion from a subcultured population is crucial to the success of a TE cornea and to making TE corneas widely available.…”
Section: D Culture Environment Results In Partial Recovery Of the Qumentioning
confidence: 99%